Posterior ankle impingement syndrome clinical features are not associated with imaging findings in elite ballet dancers and athletes - Baillie, P.; Cook, J.; Ferrar, K.; Lam, J.; Mayes, S.; Smith, P. (Journal of Science and Medicine in Sport, 2021)
Introduction: Posterior ankle impingement syndrome (PAIS) commonly presents in elite ballet and some athletic populations. Imaging is frequently used as a diagnostic tool, and imaging findings can precipitate surgical intervention. The relationship between MRI findings and clinical presentation in PAIS is unclear. This study assessed the association between clinical features and MRI findings in PAIS and compared imaging and clinical findings between participants with and without a clinical diagnosis of PAIS. Methods: Eighty-two male (54%) and female participants comprising elite ballet dancers (N=43), cricket fast bowlers (N=24) and soccer players (N=15) completed clinical assessment (posterior ankle pain, passive ankle plantarflexion test, single leg heel raise capacity test), patient reported outcome measures (Oslo Sports Trauma Research Center Overuse Injury Questionnaire, Foot and Ankle Ability Measure Sports Subscale, and Cumberland Ankle Instability Tool (CAIT)), and underwent unilateral ankle 3.0T MRI. Images were assessed for findings associated with PAIS. A subgroup of participants with a positive clinical PAIS diagnosis (posterior ankle pain plus positive ankle plantarflexion test) (N=10) were age, sex, activity, and ankle-matched to an asymptomatic participant, and clinical and imaging findings were compared between groups. Results: Imaging findings commonly associated with PAIS were prevalent despite clinical status, and were not associated with posterior ankle pain, a positive ankle plantarflexion test, or patient reported outcome measures. Imaging findings did not differ between PAIS-positive and PAIS-negative groups. The PAIS group achieved significantly fewer repetitions on single leg heel raise capacity testing (P = 0.02) and were more symptomatic for functional ankle instability according to CAIT scores (P = 0.004) than the asymptomatic group. Discussion: The lack of association between imaging findings and clinical presentation questions the role of imaging in the diagnosis and management of PAIS. It is unclear whether PAIS develops following functional (strength and/or stability) deficit, or whether strength and stability deficits are outcomes of PAIS. Clinicians should continue to rely primarily on clinical assessment in the diagnosis and management of patients with PAIS.